PENGARUH LAPORAN TANGGUNGJAWAB SOSIAL PERUSAHAAN, EPS, DAN BVS TERHADAP HARGA SAHAM DENGAN KATEGORI PERUSAHAAN SENSITIF LINGKUNGAN SEBAGAI VARIABEL MODERATING (Studi Kasus Pada Perusahaan Pertambangan yang Terdaftar di Bursa Efek Indonesia Tahun 2015-2016) - Sayogya Notohatmodjo; Dul Mu'id (Diponegoro Journal of Accounting, 2018)
This study aimed to obtain evidence about the factors that influence stock price. These factors consist of the earning per share, book value per share, corporate social responsibility disclosure. The moderating variable used environmental sensitive category. Dependent Variabel in this research is stock price at the end of the month after releasing date of financial report.The population in this study are all mining companies listed on the Indonesia Stock Exchange in 2015 and 2016. The selection method of the data used in this research is purposive sampling method. Total samples used in this study as many as 74 data. Data analysis was performed with the classical assumption and hypothesis testing with multiple regression method.The results of this study indicate that earning per share had not significant effect to stock price ,book value per share and corporate social responsibility disclosure significanly and positively effect stock price. While environmental sensitive category did not moderating effect of corporate social responsibility disclosure to stock price